2021
DOI: 10.1177/2292550321997005
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis in Plastic Surgery Correlation Between Practice and Evidence

Abstract: Background: The use of appropriate preoperative antibiotic prophylaxis decreases the risk of surgical site infections (SSI); however, the breadth of plastic surgery procedures makes it challenging to ensure appropriate use for each unique procedure type. Currently, plastic surgeons lack a cohesive and comprehensive set of evidence-based guidelines (EBG) for surgical prophylaxis. We sought to profile the perioperative antibiotic prescribing patterns for plastic surgeons in British Columbia to investigate if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
(14 reference statements)
1
14
0
Order By: Relevance
“…None of these studies nor one small randomized study could show a reduction of SSI rates through prolonged prophylaxis exceeding 24 hours after implant-based breast reconstruction. Even though a single preoperative antibiotic dose offers sufficient SSI prevention in breast augmentation surgery, extended antibiotic prophylaxis is commonly given . It is important to consider in the context of an increased risk of acquired antibiotic resistance through extended antibiotic prophylaxis .…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…None of these studies nor one small randomized study could show a reduction of SSI rates through prolonged prophylaxis exceeding 24 hours after implant-based breast reconstruction. Even though a single preoperative antibiotic dose offers sufficient SSI prevention in breast augmentation surgery, extended antibiotic prophylaxis is commonly given . It is important to consider in the context of an increased risk of acquired antibiotic resistance through extended antibiotic prophylaxis .…”
Section: Introductionsupporting
confidence: 90%
“…Even though a single preoperative antibiotic dose offers sufficient SSI prevention in breast augmentation surgery, 35 extended antibiotic prophylaxis is commonly given. 36 , 37 It is important to consider in the context of an increased risk of acquired antibiotic resistance through extended antibiotic prophylaxis. 20 The main aim of this prospective randomized clinical trial was to investigate whether single-dose or multiple-dose antibiotic prophylaxis is most effective in preventing implant removal and reducing SSI rates.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many plastic surgeons routinely prescribe 1 to 2 weeks of antibiotics after IBBR despite a lack of evidence supporting the efficacy of such a strategy to prevent or decrease SSIs. Although frequently regarded with ambivalence, prolonged prophylactic antibiotic courses are not benign; they not only confer increased cost to the health care system but also pose real risk to patients including increased systemic medication adverse effects, Clostridium difficile , as well as increased risk of drug-resistant organisms 4,8 . These risks are particularly consequential among medically vulnerable people, which include the cancer patient population undergoing IBBR.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in hip fracture surgery, a study reported almost 50 % reduction in the rate of SSI with the use of antibiotic prophylaxis compared to without [ 2 ]. However, despite best practice guidelines and the known efficacy of antibiotic prophylaxis in reducing the risk of SSI, there is evidence of wide variation in antibiotic prophylaxis practices [ 7 – 9 ]. A study involving 2,965 hospitals, including 34,133 patients, determined that only 56 % of patients received antibiotic prophylaxis within 60 min of the incision and another 20 % of the patients received antibiotics between one and two hours before incision [ 7 ].…”
Section: Introductionmentioning
confidence: 99%